Corroborative psychophysiological indices related to projective analysis of emotionality - Rosli, Asyraf (Universiti Sains Malaysia, 2012)
The present study was undertaken with an objective to determine the corroborative psychophysiological indices related to projective analysis of emotionality. Twenty six (n=26) male students of Universiti Sains Malaysia in the age ranging from 19 to 23 years volunteered as participants, who were subjected to evaluation of Psychobiological measures of tonic and phasic skin conductance activity, along with BRUMS self-report measures of mood states and projective analyses of emotionality by employing Rorschach Ink-Blot Test. Findings indicated corroborative relationships between differential psychobiological and mood states measures in predicting inner core emotionality. Dispositional emotional characteristics such as - excitability, resilience and constriction as well as tonic and phasic components of skin conductance activity were found aptly predicted by differential extents of transient facilitative, inhibitive, positive as well as negative mood state measures and faster orienting latency, which have provided us with a framework of corroborative emotional make -up.